Calcified plaque detected on OCT with deep learning and cross-validated with optical and ultrasound signals: A complementary appraisal and preamble to combined IVUS-OCT catheter - Huang, Jiayue; Ninomiya, Kai; Tu, Shengxian; Masuda, Shinichiro; Dijkstra, Jouke; Chu, Miao; Ding, Daixin; Hynes, Sean O.; O’Leary, Neil; Wijns, William; Onuma, Yoshinobu; Serruys, Patrick W. (Frontiers in Photonics, 2022)
Background The optical coherence tomography (OCT)-deep learning (DL) emerged as a promising tool for automated plaque characterization. However, its findings have not been compared with optical and ultrasound signals. Objectives The objective was to cross-validate the calcified plaque detected by OCT DL, using comprehensive tissue characterization technologies including OCT-derived optical properties, intravascular ultrasound (IVUS)-virtual histology (VH) and echogenicity. Methods Five years after bioresorbable scaffold (BRS) implantation, 15 patients underwent OCT and IVUS imaging. The unique platinum markers in BRS facilitated precise OCT-IVUS co-registration. Calcified plaque detected by OCT DL were corroborated by/with optical properties, grayscale (GS)-IVUS, IVUS-VH and echogenicity. The concordance between OCT DL and other modalities was assessed by kappa statistics. The calcium arc measured by different modalities were compared by orthogonal linear regression. Results Forty-three calcified plaques were detected by DL in 72 matched anatomic slices, 41 (95%) were confirmed as pure (n=29) or hybrid calcified plaque (n=12) by optical properties. Weighted kappa between OCT DL and GS-IVUS, IVUS-VH and echogenicity were 0.69, 0.60 and 0.60, respectively. After having excluded artifactual optical shadowing (n=5) generated by guidewire or platinum marker, kappa increased to 0.77, 0.68 and 0.69, with agreement ranging between 90% to 93%. Calcium arc derived from OCT DL showed moderate correlation and agreement with GS-IVUS (ICCa=0.81, difference=1.73±15.25°), IVUS-VH (ICCa=0.69, difference=-5.60±21.19°) and echogenicity (ICCa=0.65, difference=10.28±18.70°). Conclusions OCT empowered by deep learning showed substantial agreement with optical and ultrasound signals. The comprehensive assessment provided by OCT and IVUS heralds the potential diagnostic value of combined IVUS-OCT catheters.